PWE-041 Mannose binding lectin deficiency as a predictor of severity, disease progression and outcome following paracetamol-induced acute liver failure. (23rd September 2015) - Abeles, R; Underhill, J A; Longhi, M S; Taylor, N J; Gera, A; Shawcross, D L; Antoniades, C G; Bernal, W; Wendon, J A; Vergani, D
Abstract : Introduction: Mannose binding lectin (MBL) plays a pivotal role in the innate immune system inflammatory response. MBL deficiency (MBLdef) is caused by three single nucleotide polymorphisms (57, 54, 52) of the MBL2 gene. MBLdef is associated with poor outcomes in severe sepsis and fulminant hepatitis B. We therefore investigated whether MBLdef is a determinant of severity, disease progression and outcome following paracetamol-induced acute liver failure (PALF). Methods: 40 consecutive patients (39 Caucasian) with PALF, admitted to the liver intensive care unit of a tertiary referral centre, were recruited. Physiological, biochemical and clinical data were recorded. MBLdef was determined using polymerase chain reaction-sequence specific polymerisation. Reduced monocyte HLA-DR expression, a marker of diminished pro-inflammatory capacity, was determined by flow cytometry using dual staining with monoclonal antibodies against HLA-DR and CD14. Results: 26 (65%) patients survived. 14 (35%) died or underwent emergency liver transplantation and were identifiable at admission by greater severity of liver disease and more severe organ dysfunction, but without differences in systemic inflammatory response syndrome (SIRS) scores (2 (1–3) vs 2 (1–3)) or incidence (54% vs 57%). A significantly lower proportion (6/40, 15%) of the patients were MBLdef, compared to that expected from a large (n=353) control Caucasian population (40%, p=0.001). 3/6 (50%) MBLdef patients survived vs 23/34 (68%) of the normal MBL producers (ns). The prevalence of MBLdef was 12% (3/26) in survivors and 21% (3/14) in non-survivors (ns). MBLdef was not related to any differences in organ or liver dysfunction but was associated with lower SIRS scores (1 (0–1) vs 2 (1–2), p<0.05) and incidence (17% vs 62%, p<0.05). On admission, MBLdef was associated with a lower AST (4049 (2245–6106) vs 7897 (5141–11 113) p<0.05) and more (>45%) HLA-DRneg monocytes (50% vs 6%, p=0.003). Conclusion: Our data unexpectedly show that MBLdef may be underrepresented in patients who require tertiary referral centre care for PALF. However, MBLdef did not determine severity, disease progression and outcome in this small cohort. In those referred, MBLdef was associated with lower SIRS scores and lower HLA-DR monocyte expression, suggesting that a reduced pro-inflammatory capacity may be of importance.